Palmer Amaranth (Amaranthus palmeri) Identification and Documentation of ALS-Resistance in Argentina. Issue 2 (June 2016) - Berger, Sarah; Madeira, Paul T.; Ferrell, Jason; Gettys, Lyn; Morichetti, Sergio; Cantero, Juan J.; Nuñez, Cesar
Abstract : Palmer amaranth has greatly disrupted agricultural practices in the United States with its rapid growth and rapid evolution of herbicide resistance. This weed species is now suspected in Argentina. To document whether the suspected plant populations are indeed Palmer amaranth, molecular comparisons to known standards were conducted. Additionally, these same plant populations were screened for possible herbicide resistance to several acetolactate synthase (ALS)-inhibiting herbicides. Sequencing data confirmed that suspected populations (A2, A3, A4) were indeed Palmer amaranth. Another population (A1) was tested to determine whether hybridization had occurred between Palmer amaranth and mucronate amaranth the native amaranth species of the region. Tests confirmed that no hybridization had occurred and that A1 was simply a unique phenotype of mucronate amaranth. Each population was screened for resistance to imazapic, nicosulfuron, and diclosulam. All Palmer amaranth populations from Argentina were shown to be resistant to at least one ALS-inhibiting herbicide. The populations were then subjected to further testing to identify the mutation responsible for the observed ALS resistance. All mucronate amaranth populations exhibited a mutation previously documented to confer ALS resistance (S653 N). No known resistance-conferring mutations were found in Palmer amaranth.